Assessment of the Adaptation Capacities of the Body Based on the Determination of the Natural Antibodies to the Endogenous Bioregulators - Myagkova, M.A.; Petrochenko, S.N.; Levashova, A.I. (Biomedical Chemistry: Research and Methods, 2018)
A comparative analysis of natural antibodies to bioregulators of the excitation and inhibition nervous system (glutamate and GABA) was performed in serum of people with different types of physical activity. Immunological monitoring was done in three stages: on day 1 (stage 1), on day 14 (stage 2) and on day 28 of examination (stage 3). The study included individuals who were intensively engaged in certain kinds of sports (Greco-Roman wrestling, hockey) and volunteers, who normally practiced a set of health physical exercises. A significant increase in the level of natural antibodies to GABA and glutamate was found with an increase in the duration of exercise in the training process compared with the control group. For individuals involved in various sports activities, the relationship between the intensity of the loads and the immunological parameters was established. Practical recommendation for the application of the developed method for an estimation of adaptation possibilities of the organism at changing physical loadings is given.